2016
DOI: 10.1080/08990220.2016.1178635
|View full text |Cite
|
Sign up to set email alerts
|

Visual and proprioceptive contributions to postural control of upright stance in unilateral vestibulopathy

Abstract: Preserving upright stance requires central integration of the sensory systems and appropriate motor output from the neuromuscular system to keep the centre of pressure (COP) within the base of support (BoS). Unilateral peripheral vestibular disorder (UPVD) causes diminished stance stability. The aim of this study was to determine the limits of stability and to examine the contribution of multiple sensory systems to upright standing in UPVD patients and healthy subjects. We hypothesised that closure of the eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…We also found that balance performance was largely affected by vision and floor condition, and individuals swayed more with eyes closed, and on the unstable floor. These findings also agree well with previous findings, where impaired visual input decreases postural stability and unstable floor affects somatosensory inputs, resulting in poor balance [10,12,[23][24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 93%
“…We also found that balance performance was largely affected by vision and floor condition, and individuals swayed more with eyes closed, and on the unstable floor. These findings also agree well with previous findings, where impaired visual input decreases postural stability and unstable floor affects somatosensory inputs, resulting in poor balance [10,12,[23][24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 93%
“…For this explorative analysis, we pooled previously collected data of patients with unilateral peripheral vestibular disorder from two previous studies, the first involving a tripping while walking task 17 and the second involving stance posturography tasks. 33 For each parameter of interest (see below) we included all patients with data from each variable. In total, 12 patients were included with age, height and weight of 50.5(5.4) years, 169.7(6.6) cm and 72.5(9.6) kg respectively (means and SD).…”
Section: Methodsmentioning
confidence: 99%
“…The extrapolated CoM was defined as follows: Our previous study of stance stability assessed many variables from different sensory conditions in these patents. 33 In the current study, we include three variables and two tasks distribution normality of the results was checked prior to applying statistical analysis using the Shapiro-Wilk test, which revealed normal distributions for all parameters (P > .05).…”
Section: Insert Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during normal human movement, multiple sources of sensory information are integrated to ensure accurate positioning of the limb (assuming closed loop control). This sensory information is obtained from the visual, proprioceptive and vestibular systems (Ernst & Bülthoff, 2004; Eysel-Gosepath et al., 2016; Ponzo et al., 2018). Together, the information is integrated to create an internal representation of the body and current position of any limb (Dijkerman & de Haan, 2007; Makin et al., 2008; Tsakiris, 2010).…”
Section: Introductionmentioning
confidence: 99%